Wavelength-tunable sources of entangled photons interfaced with atomic vapours - Rinaldo Trotta (Nature Portfolio, 2016)
Quantum dots can produce entangled photons, but careful control over photon wavelength is required for real-life applications. Here, the authors use three-directional strain engineering to overcome this problem and to interface entangled photons from quantum dots with a cloud of natural atoms.